2017
DOI: 10.17219/acem/64023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anterior chamber angle in pseudoexfoliation syndrome

Abstract: Background. Pseudoexfoliation syndrome (PEX) is the most frequently identifiable cause of secondary open-angle glaucoma, known as pseudoexfoliation glaucoma. The exact pathophysiology and etiology of PEX and associated glaucoma remains obscure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Konstas et al [28] found that baseline IOP was higher in XFG patients than in POAG patients. Similar findings were reported by Tezel and Tezel [29], Lindblom and Thorburn [31], and Futa et al [32]. In addition, Teus et al [33] showed that among untreated patients, a higher level of IOP was associated with a greater loss of visual field (the MD, mean deviation coefficient, was examined).…”
Section: Pseudoexfoliation Syndrome As a Cause Of Glaucomasupporting
confidence: 79%
See 2 more Smart Citations
“…Konstas et al [28] found that baseline IOP was higher in XFG patients than in POAG patients. Similar findings were reported by Tezel and Tezel [29], Lindblom and Thorburn [31], and Futa et al [32]. In addition, Teus et al [33] showed that among untreated patients, a higher level of IOP was associated with a greater loss of visual field (the MD, mean deviation coefficient, was examined).…”
Section: Pseudoexfoliation Syndrome As a Cause Of Glaucomasupporting
confidence: 79%
“…A positive relationship was observed between intraocular pressure and the degree of pigmentation of the drainage angle in XFS and possibly with the degree of trabecular dysfunction [29].…”
Section: Pseudoexfoliation Syndrome As a Cause Of Glaucomamentioning
confidence: 84%
See 1 more Smart Citation
“…• Remains the gold standard, rather than anterior eye imaging 33,34 • Important for identifying angle closure, which may be underdiagnosed or misdiagnosed as open-angle glaucoma 35,36 • Important for identifying and prognosticating secondary causes of open-angle glaucoma (pseudoexfoliation, 37,38 angle recession, 39,40 pigmentary [41][42][43] • Important for determining suitability for laser trabeculoplasty or the need for angle closure interventions (iridotomy, lens extraction) 44 Visual field…”
Section: Gonioscopymentioning
confidence: 99%